Pliocene transverse shortening in the southern central Andes recorded in the Iglesia basin. (October 2022) - Clavel, Franco G.; Gonzalez, Marcelo; Christiansien, Rodolfo O.; Winocur, Diego; Gianni, Guido M.; Lince Klinger, Federico; Martinez, Myriam P.
Abstract: The Iglesia basin is a ∼3.5 km thick depocenter that holds an outstanding record of the late Cenozoic tectosedimentary evolution of the southern Central Andes. Previous studies have indicated an initial tectonic stage associated with NNE-striking basin-bounding faults, formed by extension in the Late Oligocene (?)-early Miocene, and a subsequent basin inversion stage in the middle-Late Miocene. We conducted a multi-disciplinary study that allowed us to unravel a conspicuous structural system orthogonal to the previous basin-bounding faults. The analysis of seismic reflection lines, satellite and local gravimetry, and field data allowed the recognition of WNW-striking thrust fault zones involving the basement and Cenozoic sedimentary cover of the Iglesia basin. Also, we document Pliocene growth strata in seismic reflection lines and intra-Pliocene thrust faults at the surface that inform the timing of transverse fault activity. Therefore, we propose new tectonic stage during the Pliocene associated with the onset of a transitory NNE-trending contractional stress field, which triggered the reactivation of inherited basement structures transverse to the main Andean strike. This indicates a transient shifting in the stress field at ∼5 Ma that we associate with a major upper-plate reconfiguration caused by the full development of the Pampean flat-slab and major plate coupling. Highlights: Iglesia basin records WNW thrust faults in the basement and sedimentary cover. A further Pliocene tectonic stage related to an NNE contractional stress field. Reactivation of pre-existent basement structures transversal to the Andes. Reconfiguration is linked to the full development of the Pampean flat-slab.